3D and 4D lithography of untethered microrobots. (July 2021) - Rajabasadi, Fatemeh; Schwarz, Lukas; Medina-Sánchez, Mariana; Schmidt, Oliver G.
Abstract: In the last decades, additive manufacturing (AM), also called three-dimensional (3D) printing, has advanced micro/nano-fabrication technologies, especially in applications like lightweight engineering, optics, energy, and biomedicine. Among these 3D printing technologies, two-photon polymerization (TPP) offers the highest resolution (even at the nanometric scale), reproducibility and the possibility to create monolithically 3D complex structures with a variety of materials (e.g. organic and inorganic, passive and active). Such active materials change their shape upon an applied stimulus or degrade over time at certain conditions making them dynamic and reconfigurable (also called 4D printing). This is particularly interesting in the field of medical microrobotics as complex functions such as gentle interactions with biological samples, adaptability when moving in small capillaries, controlled cargo-release profiles, and protection of the encapsulated cargoes, are required. Here we review the physics, chemistry and engineering principles of TPP, with some innovations that include the use of micromolding and microfluidics, and explain how this fabrication schemes provide the microrobots with additional features and application opportunities. The possibility to create microrobots using smart materials, nano- and biomaterials, for in situ chemical reactions, biofunctionalization, or imaging is also put into perspective. We categorize the microrobots based on their motility mechanisms, function, and architecture, and finally discuss the future directions of this field of research.